Crafting an African security architecture addressing regional peace and conflict in the 21st century - Besada, Hany (International political economy of new regionalisms series, 2010)
The scope and nature of humanilarian emergencies generaled by civil conflicts and wars in Africa exceed the continental capacity to adequately and effectively respond to them. With the founding of the African Union and the drafting of the Responsibility to Protect doctrine, the basis for collective action against genocide, ethnic cleansing and crimes against humanity, it is a critical time to reflect how best to address issues of regional peace and conflict. New regional conflicts around health, water, land and food security in the world's pooresl and most socially fragmented continent strengthen the need for this volume to assess African regional security arrangements, and provide new policy recommendations. -- back cover